EFEK LATIHAN FOREHAND SMASH TERHADAP PENINGKATAN KEKUATAN OTOT LENGAN PADA SISWA PUTRA KELAS X SMK NEGERI 1 TALIBURA DALAM KONTEKS TENIS MEJA - Novenrius Sini Timba, Frederiksen (Universitas Cokroaminoto Palopo, 2024)
This study aims to determine the effect of physical training on the accuracy of forehand smashes in table tennis among male students in class X at SMK Negeri 1 Talibura. The research used an experimental method with a two group pretest and posttest design. The research subjects consisted of 26 students, divided into two groups: experiment 1 (push-up training) and experiment 2 (wrist flexibility training). Data was collected through pretest and posttest forehand smash. The results showed an increase in forehand smash accuracy in both groups after training. The average pretest score for experimental group 1 was 4.4 and increased to 7.5 at posttest, while experimental group 2 increased from 4.3 to 7.6. Although the difference in effect between the two types of training is not significant, wrist flexibility training is more effective than push-ups in improving forehand smash accuracy. These results show the importance of targeted physical training in improving table tennis performance in students.